Heritage Language and Ethnic Identity: A Study on Students' Ethnic Identity and Self-Identification in Jakarta - Purnama Nancy Lumban Batu (Celt: A Journal of Culture, English Language Teaching & Literature, 2020)
This study focuses on looking at how Indonesian students view themselves as Indonesians and as members of certain ethnic groups in relation to their ability to speak in the local/heritage languages.  This article also covers their attitude towards their heritage languages in comparison to English, as a foreign language. The data for this study were collected through paper-based questionnaires and semi-structured interviews. It is found that participants with the ability to speak in their local language felt more confident in stating their ethnic identity. There was also a lead to confusion of their ethnic identities, for those few who can't speak any local language. These youths are proud Indonesians, with their Indonesian languages. However, as predicted by Rini (2014), among other languages in Indonesia, English will still be a more important foreign language. This study adds that English appears to be more important than any local language to these Indonesian students.